“JANKO”, THE “FOLK OPERA” LISZT NEVER WROTE - IVÁNYI-PAPP, Mónika (Studia Universitatis Babes-Bolyai Musica, 2014)
On the basis of his extant correspondence, Liszt planned composing an opera with Hungarian scenes and titled it Janko, der ungarische Rosshirt (Janko, the Hungarian horse-herder). The libretto suggests that the opera fell into the category of the folk play, a short-lived popular performance of the time, concerning its subject, characters, structure and music. Although he had consulted with librettists, he did not write a single line of the opera. The history of the opera could end here, but one of his composer colleagues Anton G. Rubinstein (the Russian Liszt) composed music on the basis of the libretto and called it Kinder der Heide (Children of the Moorland). Are there historical or musical traces of handing over the libretto? Could references to Hungarian music be found in Rubinstein’s music? And, is the ‘creation’ of a mixed category, the specific class of folk opera involved?